COMDORA-SBN recommendations for patients with rare kidney diseases in relation to the Covid-19 pandemic - Colares, Vinícius Sardão; Miranda, Silvana Maria; Andrade, Luis Gustavo Modelli De [UNESP]; Palma, Lilian Monteiro Pereira; Castro, Maria Cristina Ribeiro De; Silva, Cassiano Augusto Braga; Penido, Maria Goretti Moreira Guimarães; Sobral, Roberta; Vaisbich, Maria Helena (Sociedade Brasileira de Nefrologia, 2020)
During the Covid-19 pandemic, the issue is how to maintain adequate care for people with other diseases. In this document, the SBN Rare Diseases Committee (COMDORA) gives some guidelines on the care of patients with rare kidney diseases. These patients should follow the recommendations for the general population, bearing in mind that, as they have chronic kidney disease, they are included in the risk group for more serious outcomes if they develop Covid-19. Non-essential decision-making procedures should be postponed. In stable cases under appropriate treatment, we must choose to contact our patients remotely, using teleconsultations and home exam collections (if possible). In the presence of a symptom or sign of decompensation of the underlying disease, or infection with Sars-cov-2, advise the patient to seek medical assistance. The patient should not be waiting to get worse. Changes to the prescription should only be made on a scientific basis. Dosage suspension or change is not recommended, even in cases in which the patient needs to go to a center to receive his medication; in this case, the infusion center must follow the recommendations of the Ministry of Health. If the patient develops Covid-19 and uses any drugs, check the need for dose adjustment of the routine medications. Avoid the use of antimetabolics and anti-CD20 in patients with Covid-19, as they reduce viral clearance and predispose to bacterial infections. Contact between the patient and the medical team is essential; changes are recommended only with specialized medical guidance.
Keywords: Chronic kidney disease; rare diseases; Covid-19; Sars-cov-2